Biodiesel Production from Crude Jatropha Oil and Engine Performance (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
This study aimed to investigate the efficiency of converting crude Jatropha oil (CJO) into Jatropha biodiesel (JB) via the transesterification process, to optimize the operating conditions required for effective conversion, to determine the physicochemical properties of the resulting JB, and to evaluate diesel engine performance using various JB–diesel blends. Both one-step and two-step transesterification methods were explored in order to identify the most suitable approach for processing CJO. The findings revealed that only the two-step method produced satisfactory results, primarily due to the high free fatty acid (FFA) content present in the crude oil, which inhibits the effectiveness of a single-step alkaline transesterification process. Through systematic experimentation, optimal reaction conditions and variable ratios were determined, which yielded the highest biodiesel output of 84%. The optimum conditions consisted of a 0.02:1 ratio of acid catalyst to oil and a 1:1 ratio of alcohol to oil during the first step (lasting 1 hour), followed by a 0.03:1 ratio of base catalyst (NaOH) to oil and a 5:1 alcohol-to-oil ratio during the second step (lasting 2 hours). The produced JB was thoroughly characterized using Fourier Transform Infrared Spectroscopy (FT-IR), a bomb calorimeter, a density meter, and a flash point tester. The analyses established key fuel properties, with a calorific value of 35.23 MJ/kg, a density of 898 kg/m³, and a flash point of 165 °C, confirming that the biodiesel met essential quality requirements. Subsequently, blends of JB with mineral diesel at varying proportions were tested as fuel in a diesel engine to assess operational performance. Among all tested blends, the 20% JB blend demonstrated performance closely comparable to pure mineral diesel, achieving the lowest total and specific fuel consumption, while also delivering the highest engine speed, brake horsepower, and mechanical efficiency.